Investigating Causal Relationships Between Psychiatric Traits and Intracranial Aneurysms: A Bi-directional Two-Sample Mendelian Randomization Study - Peng, Peng; Chen, Zirong; Zhang, Xiaolin; Guo, Zhongyin; Dong, Fangyong; Xu, Yu; He, Yue; Guo, Dongsheng; Wan, Feng (Frontiers in Genetics, 2021)
Background Despite psychiatric traits were associated with intracranial aneurysms (IAs) in observational studies, their causal relationships remain largely undefined. We aimed to assess the causality between psychiatric traits and IAs. Methods We firstly collected the genome-wide association statistics of IAs (sample size, n = 79429) and ten psychiatric traits from Europeans, including insomnia (n =1331010), mood instability (n = 363705), anxiety disorder (n = 83566), major depressive disorder (MDD) (n = 480359), subjective wellbeing (n = 388538), attention deficit/hyperactivity disorder (ADHD) (n = 53293), autism spectrum disorder (ASD) (n = 46350), bipolar disorder (BIP) (n = 51710), schizophrenia (SCZ) (n = 105318), and neuroticism (n = 168105). We then conducted a series of bi-directional two-sample Mendelian randomization (MR) analyses, of which the Robust Adjusted Profile Score (RAPS) was the primary method to estimate the causal effects between these psychiatric traits and IAs. Results We found that insomnia exhibited a significant risk effect on IAs with the odds ratio (OR) being 1.22 (95% CI: 1.11-1.34, P = 4.61 × 10−5) from the RAPS method. There was suggestive evidence for risk effect of mood instability on IAs (RAPS, OR = 4.16, 95% CI: 1.02 -17.00, P = 0.047). However, no clear evidence of causal effects on IAs for the rest eight psychiatric traits (anxiety disorder, MDD, subjective wellbeing, ADHD, ASD, BIP, SCZ, and neuroticism) was identified. In the reverse MR analyses, no causal effects of IAs on psychiatric traits were found. Conclusions Our findings provide strong evidence for a causal risk effect of insomnia on IAs and suggestive evidence for mood instability as a causal risk effect on IAs. These results could inform the prevention and clinical intervention of IAs.